Innovation in Official Travel Administration Based on Information Technology to Support Local Government Budget Efficiency - Nur Mala Sari; Ulul Albab; Sapto Pramono; Dian Ferriswara (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze innovations in official travel administration based on information technology in supporting the efficiency of regional government budgets. This research employs a qualitative approach using the Qualitative Secondary Analysis (QSA) method by utilizing various secondary data sources, such as policy documents, government reports, and relevant research and academic journals. The results indicate that the implementation of an information technology-based official travel administration system has successfully transformed bureaucratic processes from manual to digital systems. The submission, approval, execution, and reporting of official travel, which were previously carried out through physical documents, can now be conducted through an integrated electronic system. The digitalization of administrative processes has had a significant impact on improving the efficiency of administrative service time. Employees no longer need to go through lengthy bureaucratic procedures to obtain travel approval, as the entire process can be conducted online through an application system. This aligns with the concept of digital transformation in government, which emphasizes the utilization of information technology to enhance the efficiency of public organizations. The implementation of an information technology-based official travel administration system also increases transparency and accountability in managing official travel budgets. The digital system allows all administrative processes related to official travel to be systematically recorded and electronically documented. With a digital system in place, the potential for misuse of official travel funds such as fictitious trips, duplicate activities, or manipulation of expense reports can be minimized.